On‐demand treatment with alverine citrate/simeticone compared with standard treatments for irritable bowel syndrome: results of a randomised pragmatic study. Issue 2 (21st October 2013) - Ducrotte, P.; Grimaud, J. C.; Dapoigny, M.; Personnic, S.; O'Mahony, V.; Andro‐Delestrain, M. C.
Summary Background In routine practice, irritable bowel syndrome (IBS) symptoms are often difficult to be relieved and impair significantly patients' quality of life (QoL). A randomised, double‐blind, placebo‐controlled study has shown the efficacy of alverine citrate/simeticone (ACS) combination for IBS symptom relief. Aim As IBS symptoms are often intermittent, this pragmatic study was designed to compare the efficacy of an on‐demand ACS treatment vs. that of usual treatments. Methods Rome III IBS patients were enrolled by 87 general practitioners who were randomly allocated to one of two therapeutic strategies: on‐demand ACS or usual treatment chosen by the physician. The primary outcome measure was the improvement of the IBSQoL score between inclusion and month 6. Results A total of 436 patients (mean age: 54.4 years; women: 73.4%) were included, 222 in the ACS arm and 214 patients in the usual treatment arm, which was mainly antispasmodics. At 6 months, improvement of IBSQoL was greater with ACS than with the usual treatment group (13.8 vs. 8.4; p < 0.0008). The IBS‐severity symptom score (IBS‐SSS) was lower with ACS than in the usual treatment arm with a mean (SE) decrease of 170.0 (6.6) vs. 110.7 (6.7), respectively (p = 0.0001). An IBS‐SSS < 75 was more frequent in the ACS group (37.7% vs. 16.0%; p < 0.0001). Improvement of both abdominal pain and bloating severity was also greater with the on‐demand ACS treatment, which was associated with both lower direct and indirect costs. Conclusions After 6 months, on‐demand ACS treatment led to a greater improvement of QoL, reduced the burden of the disease and was more effective for IBS symptom relief than usual treatments.